Patient-Rated Outcomes of Lumbar Fusion in Patients With Degenerative Disease of the Lumbar Spine: Does Age Matter?. Issue 10 (May 2016) - Marbacher, Serge; Mannion, Anne F.; Burkhardt, Jan-Karl; Schär, Ralph T.; Porchet, François; Kleinstück, Frank; Jeszenszky, Dezsö; Fekete, Tamás F.; Haschtmann, Daniel
Abstract : Study Design: Single-center retrospective study of prospectively collected data, nested within the Eurospine Spine Tango data acquisition system. Objective: The aim of this study was to assess the patient-rated outcome and complication rates associated with lumbar fusion procedures in three different age groups. Summary of Background Data: There is a general reluctance to consider spinal fusion procedures in elderly patients due to the increased likelihood of complications. Methods: Before and at 3, 12, and 24 months after surgery, patients completed the multidimensional Core Outcome Measures Index. At the 3-, 12-, and 24-month follow-ups, they also rated the Global Treatment Outcome and their satisfaction with care. Patients were divided into three age groups: younger (≥50 years <65 years; n = 317), older (≥65 years <80 years; n = 350), and geriatric (≥80 years; n = 40). Results: A total of 707 consecutive patients were included. The preoperative comorbidity status differed significantly ( P < 0.0001) between the age groups, with the highest scores in the geriatric group. Medical complications during surgery were lower in the younger age group (7%) than in the older (13.4%; P = 0.006) and geriatric groups (17.5%; P = 0.007); surgical complications tended to be higher in the elderly group (younger, 6.3%; older, 6.0%; geriatric, 15.0%; P = 0.09). There were no significant group differences ( P > 0.05) for the scores on any of the Core Outcome Measures Index domains, Global Treatment Outcome, or patient-rated satisfaction at either 3-, 12-, and 24-months of follow-up. Conclusion: Despite greater comorbidity and complication rates in geriatric patients, the patient-rated outcome was as good in the elderly as it was in younger age groups up to 2 years after surgery. These data indicate that geriatric age needs careful consideration of associated risks but is not per se a contraindication for fusion for lumbar degenerative disease. Level of Evidence: 4